Is the Greener Approach Better? Application of Electrochemistry in the Synthesis of Perylenediimides - Patrycja Filipek; Agata Szlapa-Kula; Stanisław Krompiec; Krzysztof Zemlak; Bartłomiej Kula; Karol Erfurt; Michał Filapek (Molecules, 2025)
Perylenediimides are an interesting group of compounds that are finding more and more applications. However, the synthetic route of obtaining and modifying them is usually very complicated, costly, and time-consuming. Therefore, the conducted research aimed to develop new, greener, electrochemical methods of obtaining unknown perylenediimides (containing 2-ethylhexyl at the nitrogen atom). For the products obtained in this way, optical and electrochemical studies were conducted and compared with DFT results (i.e., energy gaps and HOMO and LUMO levels). Asa result of optical studies, different emission wavelengths of two isomers originating from the same excitation wavelength were observed. Electrochemical studies also confirmed significant differences in properties between the obtained isomers. Spectroelectrochemical measurements were also performed; they revealed the electrochromic properties of the obtained isomers in the visible and near-infrared range. Considering all the properties (optical and (spectro)electrochemical), the obtained compounds have a high potential for use in optoelectronic devices. Moreover, unprecedented pi-expansion of cis-DBPDI via 1,2-bis(p-bromophenyl)acetylene Diels–Alder cycloaddition into the bay region was also realized successfully. Summing up, electrosynthesis and further pi-expansion via cycloaddition offer a sea of opportunities for obtaining nanographenes.